MODELING OF OIL AND OIL PRODUCTS PROCESSING AND STORAGE SYSTEM IN OIL BASES (European Journal of Emerging Technology and Discoveries, 2024)
With the rapid digitization of data and technological advancements in oil bases, there is a pressing need to innovate and enhance measurement and control processes for storing oil and petroleum products. This paper aims to model an intelligent system that mitigates errors in volume measurement processes, focusing on horizontal cylindrical reservoirs. A novel method for measuring the volume and mass of liquid products in reservoirs is proposed, leveraging microprocessors in measurement devices to revolutionize layout and operational algorithms. This approach enhances information capabilities, accuracy, reliability, and performance. The integration of microprocessors enables swift and precise measurement procedures. Results from the research demonstrate the development of an algorithm utilizing ultrasonic level measuring devices for accurately measuring the level of oil and petroleum products. Additionally, a measurement processing algorithm is devised to facilitate quick control of levels in non-stationary situations, enhancing accuracy. The study also suggests methods to further increase accuracy. Analysis of the findings highlights the potential to augment the accuracy of ultrasonic level sensors through microprocessor integration. Furthermore, it underscores the significance of modeling oil processing and storage systems in reservoirs for process optimization and operational efficiency enhancement.